The potentials of emoji in visual communication / Noorlida Daud and Ahmad Zamzuri Mohamad Ali - Noorlida, Daud; Ahmad Zamzuri, Mohamad Ali (Universiti Teknologi MARA, Perak, 2018)
Emojis are developed from emoticons and commonly used to convey emotion in online communication. It frequently assists in delivering an emotion in text-centric media such as email, media social and instant messages. This paper focuses on emojis advantages in visual communication including its effects on human's feeling. Literatures based methodology applied in this research; the datas are collected from various literatures and then analysed. From the analysis of this research, it shows other functions of emojis in persuading people in visual communication. The limitation of this study is only certain types of emojis are used and measured in delivering emotion, feeling and message from the previous researches. In future research, the potential of emojis can be expended and tested to measure its impact among users by using various types of emoji.